Heteroatom Dopants Promote Two‐Electron O2 Reduction for Photocatalytic Production of H2O2 on Polymeric Carbon Nitride. (29th June 2020) - Zhang, Peng; Tong, Yawen; Liu, Yong; Vequizo, Junie Jhon M.; Sun, Hongwei; Yang, Can; Yamakata, Akira; Fan, Fengtao; Lin, Wei; Wang, Xinchen; Choi, Wonyong
Abstract: Polymeric carbon nitride modified with selected heteroatom dopants was prepared and used as a model photocatalyst to identify and understand the key mechanisms required for efficient photoproduction of H2 O2 via selective oxygen reduction reaction (ORR). The photochemical production of H2 O2 was achieved at a millimolar level per hour under visible‐light irradiation along with 100 % apparent quantum yield (in 360–450 nm region) and 96 % selectivity in an electrochemical system (0.1 V vs. RHE). Spectroscopic analysis in spatiotemporal resolution and theoretical calculations revealed that the synergistic association of alkali and sulfur dopants in the polymeric matrix promoted the interlayer charge separation and polarization of trapped electrons for preferable oxygen capture and reduction in ORR kinetics. This work highlights the key features that are responsible for controlling the photocatalytic activity and selectivity toward the two‐electron ORR, which should be the basis of further development of solar H2 O2 production. Abstract : Heptazine‐based C3 N4 photocatalysts with heteroatom dopants exhibit potassium‐induced interlayer charge separation and local charge polarization on sulfur sites. This facilitates O2 adsorption and the subsequent two‐electron reduction of dioxygen to achieve highly efficient and selective production of H2 O2 up to a millimolar level per hour and 100 % apparent quantum yield at 420 nm.